SPECIAL EXERCISES USING THE ASSISTIVE RINGS APPARATUS AND THEIR IMPACT ON TEACHING THE FRONT AND BACK LEVER SKILLS ON THE RINGS APPARATUS (Proximus Journal of Sports Science and Physical Education, 2024)
Creating customized workouts for young athletes, ages 9 to 11, utilizing the assistive rings apparatus. 2. Creating an apparatus for assistive rings that considers the steady improvement of stability abilities on the rings. 3. Determining the effect of the unique exercises with the use of the assistive rings’ apparatus.